Dating in Light of Christ: Young Evangelicals Negotiating Gender in the Context of Religious and Secular American Culture - Irby, Courtney Ann (Sociology of religion, 2014)
Studies of young evangelicals' dating patterns tend to analyze gender by focusing on ideology. This paper suggests a view of gender and religion that examines the two institutions as interrelated by considering how and when gender and religion emerge as salient in Christian dating. Drawing on a study of young evangelicals' relationships, I explain how ideal discussions of Christian dating emerged as gender-neutral against a backdrop of secular conceptions of romantic relationships but how their personal accounts reveal a series of divergent gendered evangelical worldviews when they turn to focus on their experiences constructing relationships within the evangelical subculture. The three worldviews of idealist, independent, and ambivalent each represent different patterns of how young evangelicals emotionally understand their life as both gendered and religious indicating more complicated patterns of gender, dating, and religion than presented in previous studies.